Transgenerationally Precipitated Meiotic Chromosome Instability Fuels Rapid Karyotypic Evolution and Phenotypic Diversity in an Artificially Constructed Allotetraploid Wheat (AADD). (22nd January 2018) - Gou, Xiaowan; Bian, Yao; Zhang, Ai; Zhang, Huakun; Wang, Bin; Lv, Ruili; Li, Juzuo; Zhu, Bo; Gong, Lei; Liu, Bao
Abstract: Although a distinct karyotype with defined chromosome number and structure characterizes each biological species, it is intrinsically labile. Polyploidy or whole-genome duplication has played a pervasive and ongoing role in the evolution of all eukaryotes, and is the most dramatic force known to cause rapid karyotypic reconfiguration, especially at the initial stage. However, issues concerning transgenerational propagation of karyotypic heterogeneity and its translation to phenotypic diversity in nascent allopolyploidy, at the population level, have yet to be studied in detail. Here, we report a large-scale examination of transgenerationally propagated karyotypic heterogeneity and its phenotypic manifestation in an artificially constructed allotetraploid with a genome composition of AADD, that is, involving two of the three progenitor genomes of polyploid wheat. Specifically, we show that 1) massive organismal karyotypic heterogeneity is precipitated after 12 consecutive generations of selfing from a single euploid founder individual, 2) there exist dramatic differences in aptitudes between subgenomes and among chromosomes for whole-chromosome gain and/or loss and structural variations, 3) majority of the numerical and structural chromosomal variations are concurrent due to mutual contingency and possible functional constraint, 4) purposed and continuous selection and propagation for euploidy over generations did not result in enhanced karyotype stabilization, and 5) extent of karyotypic variation correlates with variability of phenotypic manifestation. Together, our results document that allopolyploidization catalyzes rampant and transgenerationally heritable organismal karyotypic heterogeneity that drives population-level phenotypic diversification, which lends fresh empirical support to the still contentious notion that whole-genome duplication enhances organismal evolvability.